Endocrine advantages of PD-1/PD-L1 therapy: Comparative analysis of FAERS-JADER - Yuxuan Gao; Shiyao Jiang; Yu Cui; Yumeng Wang; Lili Yu (PLoS ONE, 2026)
With the extensive clinical application of immune checkpoint inhibitors (ICIs), immune-related adverse events (irAEs) associated with these agents have increasingly garnered significant attention. Unlike other irAEs, endocrine irAEs are mostly irreversible, with variable and nonspecific symptoms, which poses challenges for clinicians in diagnosis. As a result, this study leveraged the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) and the Japanese Adverse Drug Event Report (JADER) pharmacovigilance databases to conduct an in-depth investigation into adverse events induced by PD-1/PD-L1 inhibitors, with a focus on irAEs induced by PD-1/PD-L1 inhibitors. This study pioneers the systematic cross-database validation of endocrine irAEs induced by PD-1/PD-L1 inhibitors. The integration of data from the JADER offers unique safety insights for Asian populations, bolsters global pharmacovigilance efforts, and uncovers regional variations in irAEs reporting. Notably, this study revealed a higher prevalence of endocrine irAEs among men aged over 50 years receiving PD-1/PD-L1 inhibitors. Both PD-1 and PD-L1 inhibitors are strongly associated with thyroid dysfunction, adrenal insufficiency, and pituitary inflammation. Additionally, it identifies several previously undocumented endocrine irAEs. This result unearthed safety signals hitherto unreported in drug inserts, underscoring the imperative for updating the safety labeling of PD-1/PD-L1 inhibitors with respect to endocrine irAEs. The emergence of off-label uses further underscores the need for additional clinical trials to assess their efficacy and safety.